(untitled) (Clinics, 2017)
OBJECTIVE: We describe an IncX4 pHC891/16mcr plasmid carrying mcr-1 in a colistin-resistant and carbapenem-susceptible E. coli isolate (HC891/16), ST156, which caused a blood infection in a Brazilian patient with gallbladder adenocarcinoma. METHODS: Strain HC891/16 was subjected to whole genome sequencing using the MiSeq Platform (Illumina, Inc., USA). Assembly was performed using Mira and ABACAS. RESULTS: The isolates showed resistance only to ciprofloxacin, ampicillin and cefoxitin, and whole-genome sequencing revealed the presence of aac(6’)Ib-cr and blaTEM1. CONCLUSION: Our findings warn of the possible silent dissemination of colistin resistance by carbapenem-susceptible mcr-1 producers, as colistin susceptibility is commonly tested only among carbapenem-resistant isolates.